2013
DOI: 10.1016/j.virol.2013.07.012
|View full text |Cite|
|
Sign up to set email alerts
|

Membrane-bound SIV envelope trimers are immunogenic in ferrets after intranasal vaccination with a replication-competent canine distemper virus vector

Abstract: We are investigating canine distemper virus (CDV) as a vaccine vector for the delivery of HIV envelope (Env) that closely resembles the native trimeric spike. We selected CDV because it will promote vaccine delivery to lymphoid tissues, and because human exposure is infrequent, reducing potential effects of pre-existing immunity. Using SIV Env as a model, we tested a number of vector and gene insert designs. Vectors containing a gene inserted between the CDV H and L genes, which encoded Env lacking most of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Recombinant CDV is being investigated as a delivery vector for HIV vaccines because it has the potential to specifically deliver vaccine immunogens to lymphoid tissues that are susceptible to HIV infection Zhang et al, 2013). Previous studies showed that virulent CDV replicated in the ferret gut-associated lymphoid tissues (GALT) (Pillet et al, 2009;von Messling et al, 2006), and this work extends those results by showing that a recombinant vector based on an attenuated vaccine strain also targeted the GALT.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Recombinant CDV is being investigated as a delivery vector for HIV vaccines because it has the potential to specifically deliver vaccine immunogens to lymphoid tissues that are susceptible to HIV infection Zhang et al, 2013). Previous studies showed that virulent CDV replicated in the ferret gut-associated lymphoid tissues (GALT) (Pillet et al, 2009;von Messling et al, 2006), and this work extends those results by showing that a recombinant vector based on an attenuated vaccine strain also targeted the GALT.…”
Section: Discussionsupporting
confidence: 57%
“…CDV was propagated in Vero cells and infectious virus was quantified by plaque assay. Recombinant CDV-SIVgag1 was constructed using procedures described in detail elsewhere (Zhang et al, 2013). Briefly, virus from a live attenuated vaccine based on the Onderstepoort strain was serially passaged in Vero cells after which a clonal isolate was derived by multiple rounds of plaque purification.…”
Section: Cell Culture and Virusesmentioning
confidence: 99%
See 3 more Smart Citations